The Role of MSME Workshop by KKM Tematik in Efforts to Increase Productivity of Ketapang Village Community in Mauk District - Farah Putri Oktaviani; Ahmad Kaetami; Igfar Dawam Habibi; Novrita Ramadhanti; Tarina Mei Ratna Sari; Arief Wijayakusuma; M Naufal Asyraf; M Ae Haziemill Akbar; M Zulfadli Nasution (MOVE: Journal of Community Service and Engagement, 2023)
During this COVID-19 pandemic, there are still many people whose productivity figures have decreased due to the COVID-19 that hit Indonesia since two years ago and its impact on the economy. Therefore, the Thematic Student Work Lecture (KKM) of Universita Sultan Ageng Tirtayasa is to provide workshops or training to the community to stay productive during the pandemic. The population of activities in Ketapang village is all residents but the intended target is mothers and adults in Ketapang village can be productive so that they can create jobs and can take advantage of the village's potential in the form of seafood to make frozen food such as dimsum and others. The KKM implementation method is a program oriented to community assistance in the economic field, exploring local potential, and exploring the potential of human resources. The purpose of this study was to increase the productivity of the Ketapang village community during the pandemic by holding a dimsum sales MSME workshop. Some of the results achieved were the audience's understanding of MSMEs, and providing socialization of training on how to make dim sum, as well as helping to promote citizen entrepreneurship.